2021
DOI: 10.1093/jamia/ocab225
|View full text |Cite
|
Sign up to set email alerts
|

Temporally informed random forests for suicide risk prediction

Abstract: Objective Suicide is one of the leading causes of death worldwide, yet clinicians find it difficult to reliably identify individuals at high risk for suicide. Algorithmic approaches for suicide risk detection have been developed in recent years, mostly based on data from electronic health records (EHRs). Significant room for improvement remains in the way these models take advantage of temporal information to improve predictions. Materials and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Predictive models trained for practical purposes would be designed for predicting at any point during the patient’s longitudinal history. One approach for doing this with random forests is to sample random visits in the patient’s medical timeline and include cumulative feature history up until that visit as “snapshots.” We have explored such multi-temporal suicide risk predictions with random forests in a separate study 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Predictive models trained for practical purposes would be designed for predicting at any point during the patient’s longitudinal history. One approach for doing this with random forests is to sample random visits in the patient’s medical timeline and include cumulative feature history up until that visit as “snapshots.” We have explored such multi-temporal suicide risk predictions with random forests in a separate study 10 .…”
Section: Discussionmentioning
confidence: 99%
“…To assemble the cohort for this study, we queried the MGB RPDR for 1 546 440 patients who self-identified as non-Hispanic White (i.e. 76% of the overall MGB patient population) having at least three visits after 2005, more than 30 days apart between the first and last visits, and at least one visit greater than age 10 and less than age 90, as of February 2020 (Bayramli et al, 2021; Castro et al, 2021) (see Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Random forests are popular for its ability to model complex and non-linear interactions of effects. Random forests have also proven successful in the biomedical community (Antoniadi, Galvin, Heverin, Hardiman, & Mooney, 2021;Bayramli et al, 2021;Chen & Ishwaran, 2012;Hu & Steingrimsson, 2018;Kim, Yoo, Oh, & Kim, 2013;Wongvibulsin, Wu, & Zeger, 2019).…”
Section: Random Forestmentioning
confidence: 99%